Electrical conduction behavior of high dielectric constant perovskite oxide LaxCa1-3x/2Cu3Ti4O12 - Chakravarty D.; Singh P.; Singh S.; Kumar D.; Parkash O. (My University, 2025)
In the present work, an attempt has been made to synthesize La doped calcium copper titanate, LaxCa1-3x/2Cu3Ti4O12 (x ≤ 0.50) by solid state ceramic route and study its electrical conduction behavior. The nature of conduction is studied by measuring Seebeck coefficient α as a function of temperature. It is found to be negative above 500 K indicating that electrons are the majority charge carriers. Measurements of Seebeck coefficient at lower temperatures are not reliable because of high resistance of the samples. In order to understand the mechanism of conduction, dc and ac conductivity were measured as a function of frequency and temperature. Frequency dependence of ac conductivity shows that it occurs by hopping of charge carriers among localized sites. © 2006 Elsevier B.V. All rights reserved.